Effect of permeability function on stability of residual soil slope - Tang, Angela Shi Yee (Nanyang Technological University, 2021)
Engineers often prefer to choose more conservative methods for the purpose of engineering design. Using saturated soil mechanics would result in a lower factor of safety. However, in areas like Singapore where large areas of the land mass lie above the ground water table, using saturated soil mechanics to check for the stability of nearby existing residual slopes might give the conclusion that the factor of safety is less than one even if the slope is still standing. In tropical areas such as Singapore, rainfall intensity is a critical factor that can lead to slope failure. Rainfall increases the water content of the slope during infiltration, reducing the matric suction and hence the factor of safety. The Soil-Water Characteristic Curve can give useful information about the engineering properties of the soil. The slope of the SWCC is related to the permeability function, which gives the coefficient of permeability with respect to matric suction. The permeability function is of significant interest to the study of unsaturated soil mechanics because it could give useful information about the expected rate of infiltration given the matric suction of a slope. If the permeability function and the rainfall intensity is known, it could help the civil engineering community to prevent slope failures.